A Bohr–Nikol'skii inequality. Issue 1 (2nd January 2016) - Bang, Ha Huy; Huy, Vu Nhat
ABSTRACT: In this paper, we give a new inequality called Bohr–Nikol'skii inequality which combines the inequality of Bohr–Favard and the Nikol'skii idea of inequality for functions in different metrics.